The Research on the Influence of Top Management Team Heterogeneity on Enterprise Technological Innovation - Shengguo , Guo; Die , Hu (Journal of Modern Learning Development, 2023)
This paper examines the relationship between the heterogeneity of the TMT and the company's technological innovation. The data comprising of ChiNext companies from 2012 to 2019 are selected and a system of structural equations are estimated for the study. From three aspects of heterogeneity, this paper suggests that gender and age heterogeneity have a significantly negative correlation with enterprise technological innovation, and occupational background heterogeneity has a positive effect on enterprise technological innovation. The paper also finds evidence suggesting that the ownership concentration plays a moderating role between the heterogeneity of the TMT and the company's technological innovation.